Security and Privacy Issues in Big-data Hadoop: A Review - Sathisha, MS; Ravishankar, KC (International Journal of Computer Sciences and Engineering, 2025)
Nowadays Data is one of the important assets for industries in almost all fields. Advances in information technology and its widespread growth in several areas such as business, engineering, medical, and scientific studies are resulting in data explosion. This data explosion created a new problem that, data cannot be handled by traditional techniques. This problem was, therefore, solved through the creation of a new paradigm: Big Data. Big-data refers to massive volume of structured, semi structured and unstructured data that conventional data management methods are incapable of handling. One of the finest and most popular technology available for handling and processing that enormous amount of data is the Hadoop ecosystem[4]. Enterprises are increasingly relying on Hadoop for storing their valuable data and processing it. However, Hadoop is still evolving. Many researchers have found vulnerabilities in Hadoop, which can question the security of the sensitive information that enterprises are storing on it. In order to prevent these concerns from becoming real harms, effective policy and technological measures are required on the part of organizations that uses “Big Data”, as well as for individuals to whom the data relates. It is almost impossible to carry out detailed research into the entire topic of security. In this paper we try to present a big picture of the main problems related to security in a Hadoop ecosystem, along with the possible solutions to those problems proposed by the research community.